(6t-7)(t+2)=-10

Simple and best practice solution for (6t-7)(t+2)=-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6t-7)(t+2)=-10 equation:


Simplifying
(6t + -7)(t + 2) = -10

Reorder the terms:
(-7 + 6t)(t + 2) = -10

Reorder the terms:
(-7 + 6t)(2 + t) = -10

Multiply (-7 + 6t) * (2 + t)
(-7(2 + t) + 6t * (2 + t)) = -10
((2 * -7 + t * -7) + 6t * (2 + t)) = -10
((-14 + -7t) + 6t * (2 + t)) = -10
(-14 + -7t + (2 * 6t + t * 6t)) = -10
(-14 + -7t + (12t + 6t2)) = -10

Combine like terms: -7t + 12t = 5t
(-14 + 5t + 6t2) = -10

Solving
-14 + 5t + 6t2 = -10

Solving for variable 't'.

Reorder the terms:
-14 + 10 + 5t + 6t2 = -10 + 10

Combine like terms: -14 + 10 = -4
-4 + 5t + 6t2 = -10 + 10

Combine like terms: -10 + 10 = 0
-4 + 5t + 6t2 = 0

Factor a trinomial.
(-4 + -3t)(1 + -2t) = 0

Subproblem 1

Set the factor '(-4 + -3t)' equal to zero and attempt to solve: Simplifying -4 + -3t = 0 Solving -4 + -3t = 0 Move all terms containing t to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -3t = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -3t = 0 + 4 -3t = 0 + 4 Combine like terms: 0 + 4 = 4 -3t = 4 Divide each side by '-3'. t = -1.333333333 Simplifying t = -1.333333333

Subproblem 2

Set the factor '(1 + -2t)' equal to zero and attempt to solve: Simplifying 1 + -2t = 0 Solving 1 + -2t = 0 Move all terms containing t to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2t = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2t = 0 + -1 -2t = 0 + -1 Combine like terms: 0 + -1 = -1 -2t = -1 Divide each side by '-2'. t = 0.5 Simplifying t = 0.5

Solution

t = {-1.333333333, 0.5}

See similar equations:

| 1440=x(x-18) | | 16x^4-9x^4= | | 2Q+3T=44 | | 0.3(2-3r)=2.1r+6 | | 15/5/20/3+7 | | (-2a^3/b)^5 | | 4(-2+x)=5x+1/2 | | 0.10x-0.05(34000-x)=3100 | | (2r-3)/7+(3/7)=(-r/3) | | 8y+3=6y+13 | | 4t+3(x-9)=12 | | ln(4x+3)+ln(2)=3.2 | | 2a+45-2.5(4a+21)=(a+2a+44) | | Y-7=2x+y-15 | | 7/9x+8y-8/3x-1/5y | | -.34x+12=-x+4 | | (x-8)/5+(8/5)=(-x/3) | | (4x+6)/2=15 | | (4t+1)/3=(t+5)/6+(t-3)/6 | | 4x+6/2=15 | | 68+65+x+x=360 | | 3x+3x+3x+3x=360 | | 10z+5=2(5z+8)-12 | | 59=5.6m-2.6 | | v+12-30=2 | | 5+3u-7=20 | | 5c-7=15 | | 4x-4=7x-6 | | 8+f-12=2 | | 2(x-7)-3(x+2)+4(x+1)-2=0 | | 7a=4a-9 | | 2x^2-(4-x^2)=6x-4 |

Equations solver categories